SIMULTANEOUS REVASCULARIZATION OF AORTOFEMORAL AND FEMOROPOPLITEAL ARTERIAL SEGMENTS BY SEMICLOSED LOOP ENDARTERECTOMY - V. V. Shlomin; A. V. Gusinskiy; M. L. Gordeev; I. V. Mikhailov; D. N. Maistrenko; T. B. Rakhmatillaev; D. N. Nikolaev; A. V. Shatravka; A. V. Solov’Ev; I. V. Korotkov; K. A. Komissarov; A. I. Mamedova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors would like to consider the possibility and feasibility of simultaneous revascularization of two arterial segments in patients with lower extremity arterial occlusive disease by method of semiclosed loop endarterectomy. MATERIALS AND METHODS. The research included 143 patients. Revascularization of aortofemoral segment was performed on 67 patients. The simultaneous revascularization of aortofemoral and femoropopliteal segments was carried out for 76 patients. The follow-up period was 5 years. RESULTS. There was revealed that the long-term results of multilevel reconstruction were worse that single-level reconstruction. This method requires an individual approach. The best results of simultaneous interventions were obtained in patients aged 60 and older with the III stage of chronic limb ischemia and 2 or 3 working shin arteries. The worst results were observed in patients younger than 50 year old with IV stage of critical limb ischemia and significant lesions of shin arteries.